CCR5 marks a subset of mouse hematopoietic stem cells that are myeloid primed and expand with age - Leyla Yılmaz; Allison Banuelos; Michelle Baez; Uyen Le; Nardin Georgeos; Monika Zukowska; Allison Zhang; Rahul Sinha; Irving L. Weissman (Proceedings of the National Academy of Sciences, 2026)
Hematopoietic stem cells (HSCs) are multipotent self-renewing cells that give rise to all types of blood cells. Past research has identified that long-term hematopoietic stem cells in young mice and humans produce a balanced output of lymphoid and myeloid cells, while in old age, they are largely replaced by myeloid-biased HSCs (My-HSC). It has not yet been determined whether this transition results from epigenetic changes in a single population of HSC or if two or more subsets of HSCs exist that gain or lose dominance with age via processes of selection. Whether epigenetic change or competition, several characteristics of each may exist to ensure that the appropriate subset is placed in niches that support them. HSC can be mobilized into the blood and home selectively to target tissues via expression of “homing receptors,” but these molecules do not determine their intraorgan migration to appropriate niches. Chemokines are the class of molecules that determine intraorgan migration of cells. Here, we show that the chemokine receptor CCR5 is mainly expressed on My-HSCs, and therefore, the frequency of CCR5 + HSCs increases with age. Aged HSCs negative for CCR5 expression generate lower frequency of myeloid cells than lymphoid cells upon transplantation into recipients. Additionally, disruption of the CCL5–CCR5 signaling axis changes frequency of lymphoid populations in peripheral blood of aged mice, supporting research that shows the depletion of My-HSCs can result in the rejuvenation of adaptive immunity.